Performance evaluation and investigation on mechanical properties of polyester fiber reinforced concrete - Palanisamy, T.; Dineskumar, G.; Shalini, A. (Journal of Structural Engineering, 2024)
Worldwide, a great deal of research is currently being conducted concerning the use of fiber for repair and strengthening of reinforced concrete members. The Polyester fiber has been taken for this present study due to its effective properties to control crack and increase the mechanical properties of the concrete. Concrete specimens were made for evaluation of Compressive strength, Split Tensile Strength, Flexural strength, Dynamic Young’s Modulus of Elasticity and the quality of the concrete by Non – Destructive Test (NDT). The tests were conducted at age of 7 and 28 days. Generally all mixes containing fibers achieved better properties than the control mix without fiber. Presence of fibers decreases the crack formation. By the experimental investigation the recommendations is given for using optimum percentage of Polyester fiber in concrete.